SUBLINGUAL MISOPROSTOL: A RATIONAL CHOICE FOR TREATING FIRST TRIMESTER MISSED MISCARRIAGE IN OUTPATIENT SETTINGS - Kishwar, Nasreen; Karim, Rukhsana; Samreen; Mudassir, Saman; Nazir, Laila (Journal of Postgraduate Medical Institute, 2024)
Objective: To evaluate the role of sublingual misoprostol in first trimester missed miscarriage among women seeking medical management as outpatient. Methodology: A descriptive cross sectional study was conducted at Hayatabad Medical Complex, Gynecology department, involving 179 women recruited through consecutive sampling. Eligible participants were women of reproductive age (20-40years) with singleton first-trimester miscarriage (<13 weeks gestation), residing near the hospital (at 15-30min distance) having >10Hb, hemodynamically stable and no active ongoing blood loss. The selected women received a single dose of 600 µg sublingual misoprostol in crushed form and were followed up for clinical and sonographic assessment of complete expulsion of conceptus.Data entry and analysis were performed using SPSS version 22. Results: Out of 179 women, 119 expelled the conceptus completely. Remaining patients switched over to other options due to retained products of conception or heavy bleeding.Success rate of sublingual misoprostol was found to be 66.5% .Satisfaction and acceptability is high for medical management of miscarriage 76.67% and 68.33% respectively,with statistically significant difference for satisfaction (p=0.004). Conclusion: Sublingual misoprostol is found to be effective in first trimester missed miscarriage among women seeking medical management as out patient.